Green Car Manufacturing and Stock Market Performance: Array - Ngwakwe, Collins; Musandiwa, Joseph (Acta Universitatis Danubius. Œconomica, 2022)
The quest for sustainable economic development alternatives is revolutionising the automobile industry toward a more economic and sustainable products. Objective: This paper examines the relationship between green (electric) vehicle products and stock market performance. Prior work: the paper inclines on the innovation and diffusion theory to examine green innovation in auto industry. Method: the paper adopts a fusion of review and quantitative approach. Data were from the International Energy Agency and Investing databases. A fixed effect panel analysis examine how the stock market reacts to two main types of electric vehicles – the Battery Electric Vehicle (BEV) and Plug-in Hybrid Electric Vehicle (PHEV). Result. The result adds to new knowledge namely, the BEV product relates to the stock market significantly at P=0.00002 but negatively. However, the PHEV has a positive and significant relationship with the stock market at a P=0.00001. Implication: Manufacturers introduction of more PHEV products into the consumer market has a high propensity to improve the stock market performance; this finding provides a useful information for stock markets analyst and auto industry strategic planning. It also offers a good innovation case material in business schools. Value: this paper provides the first modelling of two main types of green car on stock market performance.